EFL learners' difficulties in the structure and written expression section of TOEFL test in an Indonesian university - Saiful Akmal; Muhammad Nur Akbar Rasyid; Yuliar Masna; Cut Natasha Soraya (Englisia: Journal of Language, Education, and Humanities, 2020)
This study examined the English for Foreign Language (EFL) learners’ difficult topics in the structure and written expression section of the TOEFL Prediction Test, and reasons why they consider that these topics were difficult. A mixed-method research design was used in this study. Fifteen participants were selected through a purposive sampling mechanism from the seventh-semester students of the Department of English Language Education, Universitas Islam Negeri Ar-Raniry who have participated in the TOEFL Prediction Test to identify the difficult topics they encountered. Then, the semi-structured interviews were conducted with six underachieving student’s participants with the most recorded errors made in the test to know the reasons behind their difficulties. Findings indicated that students encountered difficulties mostly when dealing with determiners, conjunctions, adjective clauses, apposition phrases, and reduced clauses in the structure section. Meanwhile, adverb connectors, subject-verb agreement, and clause of concession, relative clause, and quantifier are the difficulties they encountered in the written expression section of the test. Thus, the findings also revealed several factors identified as the reasons behind those difficulties, namely lack of practice, grammar incompetence, vocabulary shortage, time management, and low self-confidence. Given the significant impact of this study, we suggested that the lectures and English departments should address these difficulties. It is crucial that the focus of the courses related to grammar and EFL proficiency tests be incorporated into the syllabus.